2023
DOI: 10.3390/ma16051990
|View full text |Cite
|
Sign up to set email alerts
|

FRP-Reinforced/Strengthened Concrete: State-of-the-Art Review on Durability and Mechanical Effects

Abstract: Fiber-reinforced polymer (FRP) composites have gained increasing recognition and application in the field of civil engineering in recent decades due to their notable mechanical properties and chemical resistance. However, FRP composites may also be affected by harsh environmental conditions (e.g., water, alkaline solutions, saline solutions, elevated temperature) and exhibit mechanical phenomena (e.g., creep rupture, fatigue, shrinkage) that could affect the performance of the FRP reinforced/strengthened concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…The study emphasizes the need for proper understanding of these factors to ensure the effective use of FRP materials in concrete structures and discusses serviceability criteria for FRP-reinforced concrete elements. Overall, the findings contribute to enhancing the long-term performance of RC elements using FRP materials [31]. Imjai et al introduced a new macro-mechanical model to accurately calculate the bend capacity of bent fiber-reinforced polymer (FRP) bars in reinforced concrete elements.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The study emphasizes the need for proper understanding of these factors to ensure the effective use of FRP materials in concrete structures and discusses serviceability criteria for FRP-reinforced concrete elements. Overall, the findings contribute to enhancing the long-term performance of RC elements using FRP materials [31]. Imjai et al introduced a new macro-mechanical model to accurately calculate the bend capacity of bent fiber-reinforced polymer (FRP) bars in reinforced concrete elements.…”
Section: Introductionmentioning
confidence: 93%
“…Addition of AF in concrete mixes gradually reduces the workability properties, but addition of PR in optimized AF enhances the slump value of HSC mixes made with optimum dosages of AF (Figure 3). It is concluded that the production of HSC is possible with the addition of AF without compromising the workability properties of concrete, thereby adding the PR [29][30][31][32].…”
Section: Strength Propertiesmentioning
confidence: 99%
“…The literature on the application of non-destructive testing (NDT) methods for the internal application of FRP is limited and scarce. There is no standard guide available for the inspection of FRP-RC elements [ 24 , 25 , 26 ]. This represents a knowledge gap that this research study attempts to address.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CFRP bars possess outstanding structural properties such as high tensile strength, a high strength-toweight ratio, and non-corrosive, non-magnetic attributes. The strength-to-weight ratio of CFRP bars is 10-15 times higher than that of steel bars [1][2][3][4][5][6][7][8][9][10]. Using non-corrosive FRP (fiber-reinforced polymer) bars in such constructions has proven advantageous in overcoming the issue of steel corrosion and effectively enhancing durability [11].…”
Section: Introductionmentioning
confidence: 99%